2016
DOI: 10.1186/s12889-016-3050-9
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study examining predictors of visit frequency to local green space and the impact this has on physical activity levels

Abstract: BackgroundLack of physical activity (PA) is a growing public health concern. There is a growing body of literature that suggests a positive relationship may exist between the amount of local green space near one’s home and PA levels. For instance, park proximity has been shown to predict PA levels amongst certain populations. However, there is little evidence for the role of relatedness towards nature and perceptions of local green space on this relationship. The aim of this study was to examine, in a National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 32 publications
5
84
0
4
Order By: Relevance
“…It is known that people with stronger nature relatedness tend to prefer—that is, make more frequent visits to—naturally green areas and parks [31]. In addition, environmental greenness has been found to be related to physical activity in several studies but, thus far, mainly among adults [43,44,45,46]. Our study suggested that spending time in nature was positively connected to nature relatedness, especially among those whose nature relatedness was weaker.…”
Section: Discussionmentioning
confidence: 55%
“…It is known that people with stronger nature relatedness tend to prefer—that is, make more frequent visits to—naturally green areas and parks [31]. In addition, environmental greenness has been found to be related to physical activity in several studies but, thus far, mainly among adults [43,44,45,46]. Our study suggested that spending time in nature was positively connected to nature relatedness, especially among those whose nature relatedness was weaker.…”
Section: Discussionmentioning
confidence: 55%
“…47 The practice of physical activity interacting with nature may be important for recovery of this directed attention, which is closely linked to the process of regaining balance. [48][49][50][51] The sufficiency of vitamin D has been related to the mental health of the individuals due to the presence of receptors of this vitamin in cells inside the brain, [52][53][54] also favoring their cognitive performance. 55,56 25(OH)D, in a cross-sectional analysis, was associated with the cognitive decline of subjects over 65 years.…”
Section: Figurementioning
confidence: 99%
“…However, when it comes to PA participation, the physical and perceived environment plays a central role [14]. Especially, to engage in GE, it is important that people perceive having access to safe and attractive natural environments that can support PA [15,16]. However, a systematic review of the literature emphasized that the extent to which people use available natural environments for PA purposes can also be influenced by individual determinants such as age, sex and ethnicity [10].…”
Section: Introductionmentioning
confidence: 99%